Nasal preparation prior to nasal endoscopy: a comparison of cotton pledget packing versus topical spray (Nepal Medical College Journal, 2023)
Nasal endoscopy (NE) is an office procedure done to look at the nasal and sinus passages using an endoscope which could be either rigid or flexible. It allows the clinician to characterize the intranasal anatomy better compared to the conventional techniques of headlight, speculum and mirror thus aiding the diagnosis. Therefore its popularity has increased recently and is one of the most frequently performed diagnostic procedures in Otorhinolaryngology and Head and Neck Surgery OPD. A unanimous consensus has not been reached regarding the best method for preparing the patients for NE. This study compares two methods of nasal preparation; cotton pledget packing and topical spray. A total of 100 patients were randomised into two groups of 50 each (A and B). In Group A, the nasal cavity was packed with a cotton pledget soaked in 4% lignocaine and xylometazoline nasal drops. Whereas in Group B, xylometazoline nasal drops were instilled and nasal cavity was sprayed with 10% lignocaine spray. After performing rigid nasal endoscopy, a proforma based on the patients’ and consultant’s response was filled. Patients in the cotton pledget group experienced more discomfort during packing (p=0.04), during the waiting time (p=0.001) and also during the endoscopic procedure. From the clinician’s perspective, the duration for the overall endoscopic procedure was significantly less in the spray group (p